ANALISIS LINGKUNGAN KERJA DAN SENIORITAS TERHADAP KINERJA SERTA PRODUKTIVITAS KARYAWAN PADA PERUSAHAAN - nilam purwaningtyas; Anita Kartika Sari (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2022)
This research was made based on stories and direct observations by the author. This research and analysis aims and has the intention to find out how conditions in the world of work and seniority that occur can affect employee performance and comfort. Conditions in the world of work are often interesting to discuss. Often, seniority behavior still occurs in some workplaces that are carried out by colleagues. The research entitled "Analysis of Work Environment and Seniority on Employee Performance and Productivity in Companies" aims to explore further how seniority that often occurs in companies can affect employee performance and productivity. The data used is based on research in the work environment based on the author's observations. The method used is a qualitative method.